Pengaruh Motivasi Kerja dan Keterikatan Kerja Terhadap Kinerja Karyawan pada PT. PG Rajawali I - Achmad Danish Aloeng Putra; Khoirur Rozaq (Indo Publishing, 2026)
This research was conducted against the backdrop of fluctuations in the Key Performance Indicator (KPI) values of PT PG Rajawali I during the 2021–2024 period, reflecting the dynamics of the company's performance achievements. Furthermore, observations indicate several issues related to employee performance, such as late arrivals at work, a tendency to delay task completion, increased workloads during the milling season, and errors in report preparation that require improvement. This study aims to analyze the influence of work motivation and work engagement on employee performance at PT PG Rajawali I. The study used a quantitative approach with a saturated sampling technique, so that the entire population of 64 employees was selected as respondents. Data collection was carried out through the distribution of questionnaires using a five-point Likert scale. The data obtained were analyzed using IBM SPSS Statistics through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficients of determination. The results showed that work motivation and work engagement have a positive and significant influence on employee performance, both partially and simultaneously. These findings indicate that increasing work motivation and work engagement can drive improved employee performance. Therefore, companies are expected to continue to develop various efforts that can increase employee motivation and work engagement to support the achievement of organizational goals effectively.